Unification of Law in the Marriage and Divorce Processes of the Dayak Ngaju Muslim Communities in Central Kalimantan - Tarantang, Jefry; Sururie, Ramdani Wahyu; Fautanu, Idzam (Fakultas Syariah UINSI Samarinda, 2024)
This research is a reflection of thoughts on the practice of marriage, and It examines the practices of marriage and divorce in the Dayak Ngaju tradition in Central Kalimantan. In practice, researchers found unification to be carried out autonomously in the legal system. This unification reflects a communal belief that integrates the customary law system, the positive law system, and Islamic law, particularly for Muslim communities. This study uses a non-doctrinal, empirical approach. The origin of the idea of ​​unification of the legal system was motivated by a reflection of legal thought, which found the existence of a unification of three legal systems that work respectively and have a compatibility between the legal culture of living law, formal law, and maṣlahah. The essence of the thought of unification of the legal system is evidence of new insights or a new paradigm of factual elaboration and elaboration of norms in Dayak Ngaju customary marriage and divorce. However, the implementation of Dayak Ngaju’s traditional marriage and divorce, in practice, has become a living law in the society. It means that the modern legal-positivist paradigm is unable to replace the naturalist paradigm, but both are believed by the community to be able to bring the parties towards the philosophical goal of law, namely peace (maṣlahah).